Multiple Vickrey Auctions for Sustainable Electric Vehicle Charging - Valogianni, Konstantina; Gupta, Alok; Ketter, Wolfgang; Sen, Soumya; Heck, Eric van (International Conference on Information Systems (ICIS), 2019)
Electric vehicles (EVs) are important contributors to a sustainable future. However, uncontrolled EV charging in the smart grid is expected to stress its infrastructure, as it needs to accommodate extra electricity demand coming from EV charging. We propose an auction mechanism to optimally schedule EV charging in a sustainable manner so that the grid is not overloaded. Our solution has lower computational complexity, compared to state-of-the-art mechanisms, making it easily applicable to practice. Our mechanism creates electricity peak demand reduction, which is important for improving sustainability in the grid, and provides optimized charging speed design recommendations so that raw materials are not excessively used. We prove the optimal conditions that must hold, so that different stakeholder objectives are satisfied. We validate our mechanism on real-world data and examine how different trade-offs affect social welfare and revenues, providing a holistic view to grid stakeholders that need to satisfy potentially conflicting objectives.
Keywords: Electric mobility; Green IS; Sustainability; Intelligent agents; Smart markets; 33 Ciencias Tecnológicas; ODS 7 - Energía asequible y no contaminante